2003
DOI: 10.1161/01.hyp.0000073062.29546.01
|View full text |Cite
|
Sign up to set email alerts
|

Early Autonomic Dysfunction in Glucose-Tolerant but Insulin-Resistant Offspring of Type 2 Diabetic Patients

Abstract: Abstract-In type 2 diabetes, both insulin resistance and hyperglycemia are considered responsible for autonomic dysfunction, but the specific role of these two abnormalities is not clear. To test the specific role of insulin resistance on autonomic dysfunction, we studied 69 glucose-tolerant offspring of type 2 diabetic patients, comparing the most insulin-resistant tertile (IR) with the most insulin-sensitive tertile (IS) and comparable control subjects, all undergoing the oral glucose tolerance test, impeden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Glucocorticoids have a diabetogenic function that interferes with insulin action in different levels, such as dysfunction in glucose transport to intracellular space through GLUT4 (32). The increased insulin levels could be explained by SANS hyperactivity, which release noradrenaline and will bind to pancreatic β2-adrenergic receptor, producing increased release of insulin (33).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have a diabetogenic function that interferes with insulin action in different levels, such as dysfunction in glucose transport to intracellular space through GLUT4 (32). The increased insulin levels could be explained by SANS hyperactivity, which release noradrenaline and will bind to pancreatic β2-adrenergic receptor, producing increased release of insulin (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has shown that the offspring of individuals with type 2 diabetes have an increased risk of developing type 2 diabetes, with defects in early beta cell secretion [22][23][24][25]. It has also been suggested that these offspring have early autonomic dysfunction, even in the absence of glucose intolerance [26], and more often display metabolic abnormalities with high insulin levels and arterial hypertension [27,28]. In a previous community-based cohort, parental diabetes appeared to be an independent predictor of longitudinal changes in both systolic and diastolic BPs in the offspring, regardless of race and sex [29].…”
Section: Discussionmentioning
confidence: 99%
“…21 Interestingly, insulin resistance is associated with abnormal control of blood pressure and sympathetic activation even in the healthy offspring of T2DM patients. 22 Our study cohort included subjects who did not have any previously known abnormality in glucose tolerance but the OGTT revealed that 17% of them showed impaired glucose regulation. Majority of them were in the pre-diabetes state and only a few of them were T2DM patients.…”
Section: Discussionmentioning
confidence: 99%